Variants in the Upstream Region of the Insulin Receptor Substrate-1 Gene Is Associated with Major Depressive Disorder in the Han Chinese Population - Wang F (Dove Medical Press, 2020)
Fan Wang,1,2 Shunying Yu,3 Rubai Zhou,1 Ruizhi Mao,1 Guoqing Zhao,1,4 Xiaoyun Guo,1 Qingqing Xu,3 Jun Chen,1 Chen Zhang,1 Yiru Fang1,5,6 1Division of Mood Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai 200030, People’s Republic of China; 2Department of Psychiatry and Cellular & Molecular Medicine, University of Ottawa Institute of Mental Health Research at the Royal, Ottawa, ON, Canada; 3Department of Genetics, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai 200030, People’s Republic of China; 4Department of Psychology, Provincial Hospital Affiliated to Shandong University, Jinan 250021, People’s Republic of China; 5Shanghai Key Laboratory of Psychotic Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai 200030, People’s Republic of China; 6Brain Science and Technology Research Center, Shanghai Jiao Tong University, Shanghai 200240, People’s Republic of ChinaCorrespondence: Yiru FangClinical Research Center & Division of Mood Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, CAS Center for Excellence in Brain Science and Intelligence Technology Shanghai Key Laboratory of Psychotic Disorders, 600 South Wanping Road, Shanghai 200030, People’s Republic of ChinaTel +86-21-3428 9888 Ext 3529Fax +86-21-64387986Email yirufang@aliyun.comChen ZhangDivision of Mood Disorders, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, 600 South Wanping Road, Shanghai 200030, People’s Republic of ChinaEmail zhangchen645@gmail.comIntroduction: Major depressive disorder (MDD) is one of the most prevalent and disabling mental disorders, although its underlying genetic mechanism remains unknown. Insulin receptor substrate-1 (IRS-1) is one of the critical downstream molecules in the insulin resistance signaling pathway, linking depression and diabetes. Therefore, we hypothesized that IRS-1 would be a susceptible gene for MDD, and we aimed to examine the genetic association between IRS-1 and MDD.Methods: This case-control study included 583 patients with MDD and 564 controls, and the genotypic and allelic distributions of the IRS-1 gene’s four single nucleotide polymorphisms (SNPs) were detected by TaqMan SNP genotyping technology. Of the 583 patients, 191 underwent a further detailed interview about symptom severity and family history of mental illness. The chi-square or t test was used to analyze the data, and analyses were performed using SPSS19.0 software.Results: A haplotype in the 5ʹ-upstream region of IRS-1 consisting of rs13411764 and rs3820926 was a risk factor of MDD. Patients with a family history of mental illness were more likely to have a GG genotype in rs13411764 and a G-T haplotype containing rs13411714-rs3820926.Discussion: The findings imply that the haplotype consisting of rs13411764 and rs3820926 in the upstream of IRS-1 is a risk factor for MDD. This haplotype could affect IRS-1 expression levels, and it is mostly inherited from parents. Thus, the presence of variants in the upstream region of IRS-1 is a risk factor of MDD, and this study could serve as a convincing reference for further studies.Keywords: major depressive disorder, IRS-1, single nucleotide polymorphisms, haplotype, family history